2015
DOI: 10.1098/rsta.2014.0451
|View full text |Cite
|
Sign up to set email alerts
|

The East Siberian Arctic Shelf: towards further assessment of permafrost-related methane fluxes and role of sea ice

Abstract: Sustained release of methane (CH4) to the atmosphere from thawing Arctic permafrost may be a positive and significant feedback to climate warming. Atmospheric venting of CH4 from the East Siberian Arctic Shelf (ESAS) was recently reported to be on par with flux from the Arctic tundra; however, the future scale of these releases remains unclear. Here, based on results of our latest observations, we show that CH4 emissions from this shelf are likely to be determined by the state of subsea permafrost degradation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
210
0
11

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(231 citation statements)
references
References 38 publications
10
210
0
11
Order By: Relevance
“…Since then, oceanographic campaigns have been organized, especially to sample bubbling areas. For instance, Shakhova et al (2010Shakhova et al ( , 2014 infer 8-17 Tg CH 4 yr −1 emissions just for the East Siberian Arctic Shelf (ESAS), based on the extrapolation of numerous but local measurements, and possibly related to melting seabed permafrost (Shakhova et al, 2015). Because of the highly heterogeneous distribution of dissolved CH 4 in coastal regions, where bubbles can reach the atmosphere, extrapolation of in situ local measurements to the global scale can be hazardous and lead to biased global estimates.…”
Section: Oceanic Sourcesmentioning
confidence: 99%
“…Since then, oceanographic campaigns have been organized, especially to sample bubbling areas. For instance, Shakhova et al (2010Shakhova et al ( , 2014 infer 8-17 Tg CH 4 yr −1 emissions just for the East Siberian Arctic Shelf (ESAS), based on the extrapolation of numerous but local measurements, and possibly related to melting seabed permafrost (Shakhova et al, 2015). Because of the highly heterogeneous distribution of dissolved CH 4 in coastal regions, where bubbles can reach the atmosphere, extrapolation of in situ local measurements to the global scale can be hazardous and lead to biased global estimates.…”
Section: Oceanic Sourcesmentioning
confidence: 99%
“…Moreover, the first results from offshore drilling (accomplished from the fast ice in April 2011) down to 52 m below the sea floor in the southeastern Laptev Sea showed that the sediment core was entirely unfrozen, and 8-12 • C warmer than an on-land sediment core obtained in the nearby Chay-Tumus borehole (Shakhova et al, 2014), confirming these authors' modeling results. Besides, a major portion (> 80 %) of the Russian Arctic shelf is underlain by subsea permafrost; this permafrost has been degrading at increasing rates during the last 30 years, releasing organic carbon (OC) and pre-formed methane (CH 4 ) stored within and beneath subsea permafrost (Shakhova et al, 2017). Seafloor erosion could start from initial ground ice melt followed by formation of a polygonal form of seafloor landscape.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors suggest that it would take ∼ 5-7 millennia for subsea permafrost to reach thaw point (Romanovskii et al, 2005), meaning that the coastal subsea permafrost is still stable. Others believe that in the coastal areas of the shallow Siberian Arctic seas, where permafrost was submerged most recently, taliks (layers or columns of thawed sediments within permafrost) might form as a result of the combined effect of geothermal flux from fault zones, the warming effect of rivers and overlying seawater, and the already present thermokarst Shakhova et al, 2009Shakhova et al, , 2015Nicolsky and Shakhova, 2010; Figure 1. A view of the Arctic hydrological cycle showing key links between land, ocean, and atmosphere (modified from http://arcticchamp.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations